Hypertrophic gastropathy with gastric adenocarcinoma: Menetrier's disease and lymphocytic gastritis?. Issue 12 (December 1991) - Mosnier, J F; Flejou, J F; Amouyal, G; Gayet, B; Molas, G; Henin, D; Potet, F
Abstract : Lymphocytic gastritis is a form of gastric inflammation characterised by a pronounced increase in lymphocytes in gastric surface and foveolar epithelium. Lymphocytic gastritis is often associated with endoscopic evidence of 'varioliform gastritis'. Lymphocytic gastritis has recently been reported to be associated with other forms of hypertrophic gastropathies. We present a case of hypertrophic gastropathy with gastric adenocarcinoma, with both Menetrier's disease and lymphocyte gastritis. Immunohistochemical studies showed that the intraepithelial lymphocytes were predominantly alpha/beta T cells as in the normal stomach and not gamma/delta T cells as in coeliac sprue. This case together with the six recently published cases suggests that Menetrier's disease and lymphocytic gastritis may be part of the same disease spectrum.